Islam : an illustrated journey - Daftary, Farhad; Hirji, Zulfikar A. (Zulfikar Amir), 1965-; Institute of Ismaili Studies (London : Azimuth Editions in association with The Institute of Ismaili Studies, 2018)
c
In Abraham's footsteps -- God's messenger -- God's revelation -- Succession and the early caliphates -- Rivals and revolutionaries -- Muslim renaissance -- Introspection and invasion -- Last empires -- Modern Muslims.
Published'in commemoration of the Diamond Jubilee of His Highness Aga Khan'.
Includes bibliographical references (pages 332-333) and index.
Keywords: Islam -- History; Islamic civilization -- History; Islamic civilization -- History -- Pictorial works; Islamic Empire -- History